Scanning Small-Angle X-Ray Scattering Tomography - Feldkamp, Jan Moritz (Saechsische Landesbibliothek- Staats- und Universitaetsbibliothek Dresden, 2009)
The techniques of small-angle x-ray scattering (SAXS) and grazing-incidence small-angle x-ray scattering (GISAXS) have successfully been used for many years in the analysis of nanostructures in non-crystalline samples, e.g., polymers, metallic alloys, ceramics, and glasses. In many specimens, however, the nanostructure is not distributed homogeneously, but instead varies as a function of position in the sample. Conventional SAXS or GISAXS measurements on such heterogeneous samples merely yield an averaged scattering pattern of all the different structures present along the x-ray beam path. In this thesis, scanning tomography is combined with SAXS and GISAXS, revealing the individual local scattering cross section at each position on a virtual section through the sample. The technique thereby offers unique analytical possibilities in heterogeneous specimens.